Orally administered ketoconazole: route of delivery to the human stratum corneum. - Harris, R (1983)
Delivery of ketoconazole to human stratum corneum was studied. Thirteen healthy volunteers, three patients with chronic fungal disease and one patient with palmar-plantar hyperhidrosis were given 400 mg of ketoconazole daily for various lengths of time. The ketoconazole content of palmar stratum corneum, eccrine sweat, sebum, and serum was measured by high-pressure liquid chromatography (sensitivity, 0.005 to 0.010 microgram/ml). Palmar stratum corneum obtained after 7 and 14 days of daily administration contained up to 14 micrograms of ketoconazole per g. Ketoconazole was not found in sebum after 7 or 14 days of daily ingestion of the antimycotic agent. Sebum from three patients with chronic fungal infection treated for greater than 9 months contained ketoconazole (means, 4.7 micrograms/g). Thermogenic whole body eccrine sweat contained a mean of 0.059 microgram/ml on day 7 and 0.084 microgram/ml on day 14 of daily administration. Ketoconazole appeared in thermogenic whole body eccrine sweat and palmar hyperhidrotic sweat within 1 h after a single oral dose. Partition studies of ketoconazole containing eccrine sweat demonstrated a 10-fold greater concentration in the sediment phase (desquamated keratinocytes) compared with the clear supernatant phase. In vitro studies with [3H]ketoconazole-supplemented supernatant sweat revealed preferential binding to stratum corneum, hair, and nails and its partitioning to lipid-rich sebum. We conclude that eccrine sweat rapidly transports ketoconazole across the blood-skin barrier, where it may bind or partition to keratinocytes and surface lipids.